How to Increasing Memorable Tourism Experiences at Heritage Destination - Saryatun Saryatun; Sulis Riptiono; Siti Nur Azizah; Intan Muliana Rhamdhani (UM Purwokerto Press, 2024)
Background: This study aims to investigate the effect of destination image, self-congruity, and visitor engagement on memorable tourism experiences. Method: Tourists who visited Borobudur Temple were used as respondents who were taken using convenience techniques, as many as 150 questionnaires were distributed and analysed using multiple linear regression analysis with the SPSS version 28 statistical tool. Results: The results showed that all the hypotheses tested in this study were accepted. Image destinations play the most important role in increasing MTE, next are visitor engagement and self-congruity. The results of this study provide evidence that the tourist experience is an important emotional element for visitors to interact in their tourism activities. The substantial of the destination image, self-congruity, and visitor engagement will further increase the MTE. Conclusion: The antecedents of Memorable Tourism Experiences that exam in this research is an important element for the tourism business so that it can foster memories and memorable experiences for visitors when they carry out tourism activities.